Efeitos de manipulações ascendentes e descendentes sobre a comunidade fitoplanctônica em um reservatório eutrófico no semi-árido brasileiro - Dantas, Danyhelton Douglas Farias (2009)
Top-down (grazing) and bottom-up (nutrient, light) controls are important in freshwater ecosystems regulation. Relative importance of these factors could change in space and time, but in tropical lakes bottom-up regulation has to been appointed as more influent. Present study aimed to test the hypothesis that phytoplankton growths rate in Armando Ribeiro reservoir, a huge eutrophic reservoir in semi-arid region of Rio Grande do Norte state, is more limited by nutrient available then zooplankton grazing pressure. Bioassay was conduced monthly from September (2008) to August (2009) manipulating two levels of nutrients (with/without addition) and two level of grazers (with/without removal). Experimental design was factorial 2X2 with four treatments (X5), (i) control with water and zooplankton from natural spot ( C ), (ii) with nutrient addition ( +NP ), (iii) with zooplankton remove ( -Z ) and (iv) with zooplankton remove and nutrient addition ( -Z+NP ). For bioassay confection transparent plastic bottles (500ml) was incubate for 4 or 5 days in two different depths, Secchi`s depth (high luminosity) and 3 times Secchi`s depth (low luminosity). Water samples were collected from each bottle in begins and after incubates period for chlorophyll a concentration analysis and zoopalnktonic organisms density. Phytoplankton growths rates were calculated. Bifactorial ANOVA was performance to test if had a significant effect (p<0,005) of nutrient addition and grazers remove as well a significant interaction between factors on phytoplankton growths rates. Effect magnitude was calculated the relative importance of each process. Results show that phytoplankton growth was in generally stimulated by nutrient addition, as while zooplankton remove rarely stimulated phytoplankton growth. Some significant interactions happening between nutrient additions and grazers remove on phytoplankton growth. In conclusion this study suggests that in studied reservoir phytoplankton growth is more controlled by ascendent factors than descendent